On Online Assignments in a Calculus Class - Jungic, Veselin; Kent, Deborah; Menz, Petra (Journal of University Teaching and Learning Practice, 2012)
In this paper, we describe our experience with the creation and utilization of online assignments for several calculus classes at Simon Fraser University (SFU). We present our findings regarding available software by considering the needs and perspectives of the instructors, students, and administrators. We provide a list of questions that guide an instructor in choosing online assignment problems and a list of benefits that are the natural outcome of this endeavor. We analyze survey data from our science/engineering calculus as well as social science calculus courses over the span of five years. As a conclusion we propose a balanced use of both paper and online assignments in teaching introductory calculus classes. Finally, we discuss recent developments and future possibilities of utilizing online problems.